Nuances in the Management of Rhinophyma - Little, Stewart C.; Stucker, Fred J.; Compton, Andrew; Park, Sunny S. (Facial Plastic Surgery, 2012)
Rhinophyma is a cosmetically disfiguring disease of the external nose that most frequently affects elderly Caucasian males. Frequently, there is associated derangement of nasal airway patency. Although the true incidence of rhinophyma and its exact etiology remain unknown, it is widely believed to represent the final stage in a continuum of acne rosacea. Medical therapy has not been effective in reversing the disease process, and surgery remains the most accepted method of treating rhinophyma. A wide variety of surgical techniques have been developed and modified over the years in an effort to treat this disorder safely and without significant sequelae. Despite many advances in fundamental understanding, surgical techniques, and related technologies, no single method has been universally embraced and employed as the “gold standard.” This review describes the most commonly employed modern surgical techniques and methods used throughout the world to treat rhinophyma. There is special emphasis on the authors' preferred method of excision and postoperative management (tumescent anesthesia, Weck blade excision, and argon beam coagulation), which has been demonstrated to be effective and expeditious.
Keywords: rhinophyma; acne rosacea; argon beam coagulator; Weck blade